2020
DOI: 10.1038/s41598-020-76739-2
|View full text |Cite|
|
Sign up to set email alerts
|

Association between pet ownership and physical activity levels, atopic conditions, and mental health in Singapore: a propensity score-matched analysis

Abstract: Although existing literature increasingly suggests a positive influence of pet ownership on human physical activity levels, results from many European, American, and Japanese studies have been inconsistent. How pet ownership impacts mental health and atopy is likewise controversial and whether distinct demographic subgroups experience differential effects is unclear. This cross-sectional study surveyed participants (n = 823) via a self-administered online questionnaire. Comparisons of outcomes between pet owne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 68 publications
1
13
1
Order By: Relevance
“…In our previous study before these measures were implemented, pet owners reported higher moderate- and vigorous-intensity physical activity levels than non-pet owners, likely attributable to caregiving- and pet-related activities [ 17 ]. The present study did not reproduce these findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study before these measures were implemented, pet owners reported higher moderate- and vigorous-intensity physical activity levels than non-pet owners, likely attributable to caregiving- and pet-related activities [ 17 ]. The present study did not reproduce these findings.…”
Section: Discussionmentioning
confidence: 99%
“…The full questionnaire used was previously published [ 17 ]. We collected participant data on sociodemographic profile, past medical history, pet ownership and attachment levels, physical activity levels and self-perceived general and mental health.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors such as cultural/ethnic identity, gender identity, marital and family status, socioeconomic status, and housing type all contribute to the family system, but are not consistently controlled for in studies on pet ownership (Kazdin, 2015;Purewal et al, 2017;Rodriguez, Herzog, & Gee, 2021). In fact, several studies have found that health effects associated with pet ownership were attenuated or changed when controlling for confounding variables (Goh et al, 2020;Jacobson & Chang, 2018;Marsa-Sambola et al, 2016;Miles, Parast, Babey, Griffin, & Saunders, 2017) or assessing interactions between pet ownership and demographic variables (Liu et al, 2019;Stanley et al, 2014). To inform evidence-based demographic covariates for pet ownership studies, several studies in the United Kingdom have specifically assessed the sociodemographics of pet ownership (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We postulate that lifestyle differences due to ethnic and cultural diversities may influence house dust microbiome composition. For instance, a higher proportion of Singaporean Malays are pet owners (including cats, small mammals and birds) as compared with other races (Goh et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%